UMPSA receives a visit from the President of the Malaysian Board of Technologists - Mimi Rabita, Abd Wahit (UMPSA, 2023)
GAMBANG, 27 October 27 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) received a delegation visit from the Malaysian Board of Technologists (MBOT) led by its President, Datuk Ts. Ir. Dr. Siti Hamisah Tapsir, FASc.